Salivary Scca1, Scca2 and Trop2 in Oral Cancer Patients-A Cross-Sectional Pilot Study - Ivana Karmelić; Ivan Salarić; Ksenija Baždarić; Marko Rožman; Ivan Zajc; Marinka Mravak-Stipetić; Ivona Bago; Davor Brajdić; Jasna Lovrić; Darko Macan (MDPI AG, 2022)
Oral squamous cell carcinoma (OSCC) is frequently diagnosed in the advanced stages. The purpose of this paper is to determine the salivary values of SCCA1, SCCA2 and TROP2 in patients with T1N0M0 OSCC and to compare them with the values obtained from healthy individuals. Unstimulated (UWS) and stimulated (SWS) saliva was sampled from 29 patients with T1N0M0 OSCC and 29 sex- and age-matched healthy individuals. Statistical difference was observed in SCCA1 and SCCA2 levels both in UWS and SWS samples. TROP2 was not measurable in most of the salivary samples. Both SCCA1 and SCCA2 could represent potential biomarkers for the early-stage OSCC. Research on a larger sample and biomarker validation is needed to assess the clinical potential of SCCA1 and SCCA2 in the OSCC early diagnostics.